Penggunaan Teknologi Multimedia Pada Pembelajaran Literasi Anak Usia Dini - Novitasari, Khikmah (Jurnal Golden Age, 2019)
This study was aimed to describe the use of multimedia technology for literacy learning in early childhood education, including: implementation of multimedia technology utilization in children?s literacy learning. This study was a qualitative research. Data collection used observation techniques, interviews and document review. The data validity was obtained through triangulation. The data analysis technique was done using interactive model. The results show that: Implementation of use of multimedia technology in literacy learning was implemented in each step of learning centers with steps:(a) focusing attention, (b) orientation, (c) modeling, (d) child play stage, and (e) summary.